Personality, anxiety and information behavior in social media : a cognitive vulnerability approach - Chua, Junjie (2014)
While social media can be a useful source of information to help one keep abreast of developments of events happening locally and globally, studies have also suggested that frequent use of social media can cause anxiety. Building on the research that negative news in the mass media can induce anxiety symptoms (e.g., Johnston & Davey, 1997) and that negative content in social media can trigger anxiety-motivated information behaviours (e.g., Chen & Sakamoto, 2013), this study explores the possible extension of such behaviours in the context of negative information in social media. To identify possible groups of vulnerable individuals susceptible to such anxiety and information behaviours, the cognitive vulnerability to anxiety theoretical framework is adopted. More specifically, two cognitive vulnerabilities to anxiety variables: intolerance of uncertainty and looming cognitive style are studied. These are negative beliefs which propel one to experience anxiety symptoms due to specific cognitive appraisal biases when one is exposed to threat relevant information. The study was conducted using the survey questionnaire. A self-reported questionnaire method known as the situation response inventory was also used to measure participants’ levels of anxiety symptoms and information behaviour intentions in reaction to negative social media information. In all, 177 samples were gathered and analysed using the convenience sampling method.